The Association of Demographic Factors Among Ex-Female Sex Workers and Non-Female Sex Workers in Ex-Localization Area - Angkawidjaja, Merry Apriliani; Wardhana, Ardyan Prima; Dahliana, Anita (Jurnal Psikiatri Surabaya, 2023)
Introductions: The localization of Female Sex Workers (FSW), one of the largest in Southeast Asia, has considerably reduced because of the government's actions since 2014. Minimal research reported on the association factor among ex-FSW and non-FSW. Objectives: This study aimed to determine the association of demographic factors among ex-FSW and non-FSW in the ex-localization area. Methods: This was a cross-sectional study to identify the association of demographic factors among ex-FSW and non-FSW in the ex-localization area in Surabaya, Indonesia. Seventy-five participants met inclusion criteria and were gathered at predetermined locations on December 10th, 2022, to complete demographic data. Also, they had completed Beck Depression Inventory (BDI) tests for screening the clinical depression assessment. Data analysis was performed using the SPSS 24 software. Results: The study determined associated factors within the ex-FSW (p<0.05) in terms of marital status (0.03), history of psychiatric disorders (0.01), and history of smoking (0.02). The clinical depression assessment was higher in the ex-FSW group (22.5%) than in the non-FSW group (11.43%). Conclusions: Based on the work history of FSWs and non-FSWs, it had been found associated in terms of marital status, history of psychiatric disorders, and smoking history. Also, the Clinical Depression occurred more in the ex-FSW than the non-CSW group.